How Nanoparticles Transform Single Molecule Measurements into Quantitative Sensors. Issue 18 (30th September 2019) - Wu, Yanfang; Bennett, Danielle; Tilley, Richard D.; Gooding, John Justin
Abstract: Single molecule measurements are revolutionizing the understanding of the stochastics of behavior of single molecules. There is a common theme referred to as a near‐field approach, in how many single molecule measurements are being performed in assays. The term near field is used because the measurement volume is typically very small such that a single molecule, or a single molecule binding pair, within that volume is of an appreciable concentration. The next development in detection will be performing many single molecule measurements at one time such that single molecule measurements can be used as the basis for quantitative analysis. There have already been some notable developments in this direction. Again, all have a common theme in that nanoparticles are used to create many near‐field volumes that can be measured simultaneously. Herein, the coupled developments in nanoparticles and measurement strategies that allow nanoparticles to be the backbone of the next generation of sensing technologies are discussed. Abstract : The emerging applications of nanoparticle‐enabled single‐molecule detection are introduced. The recent advances in the development of single‐nanoparticle assays for quantitative analysis as well as multiplexed detection are summarized. The key challenges and the prospects in this exciting field of research are also highlighted.